Surveillance via wastewater monitoring and nasal self-collection of specimens (The SWANSS Study): a CFIR-informed qualitative study with key carceral and healthcare stakeholders - Kyler N. Moore; Patrick M. Bircher; Emily A. Ogutu; Shanika S. Kennedy; Victoria M. Brown; Matthew C. Freeman; Victoria L. Phillips; Anne C. Spaulding; Matthew J. Akiyama (BMC Public Health)
Abstract Background Implementing public health interventions can be challenging in carceral settings. Jails are institutions with the shortest lengths of stay, resulting in frequent turnover and constantly shifting populations. Jails had particularly acute challenges during the early stages of the COVID-19 pandemic when incarcerated persons were highly susceptible to infection and severe disease. The purpose of this study was to identify barriers and facilitators to wastewater-based surveillance (WBS) and nasal self-testing (NST) as a combined strategy of COVID-19 surveillance in Fulton County Jail (FCJ), Atlanta, Georgia. Implications for efficient and effective infectious disease testing among this susceptible population are relevant for ongoing surveillance of current endemic pathogens and future epidemics. Methods We utilized a multilevel, theory-informed qualitative approach to conduct semi-structured one-on-one and small group interviews with nine distinct jail stakeholder groups: jail custody leadership, administrators, officers, maintenance workers, Georgia Department of Health’s COVID-19 testing contractor, jail health care leaders, nursing staff, laboratory leadership, and staff. Interview guides and analyses were informed by the Consolidated Framework for Implementation Research (CFIR). We used Applied Thematic Analysis to identify domains within CFIR reflecting barriers and facilitators to WBS combined with NST in large urban jail settings. Results Twelve interviews were conducted with administrative, healthcare, maintenance, custody, and laboratory personnel from July 2022 to November 2022. Seven CFIR constructs were identified as barriers, sixteen as facilitators, and one as a neutral factor for the implementation of WBS combined with NST. Jail stakeholders underscored the relative advantage of self-testing, highlighted limited resources, and expressed concerns for the sustainability of WBS due to competing priorities. Many of the stakeholders within the jail setting that were interviewed had hierarchical organizational structures, which made decision-making processes regarding WBS and NST complex and challenging to implement. Conclusions Given the political, structural, and organizational factors in a jail setting, innovations such as NST and WBS require a rigorous implementation strategy supported by ongoing engagement and collaboration with a multitude of stakeholders.